ANALYSIS OF THE INFLUENCE OF INFORMATION TECHNOLOGY AND INNOVATION ON COMPETITIVE EXCELLENCE TO IMPROVE ORGANIZATIONAL PERFORMANCE ( CASE STUDY ON THE ATTRACTIONS OF BUKIT PANEMBONGAN VILLAGE TEMBONG KUNINGAN REGENCY) - Wely Hadi Gunawan; Wachyuni Wachyuni (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Tourism is one of the uses of natural resources that can have high economic value for regions that manage natural resources into tourist attractions that can attract visitors both from within and outside the country. In addition, tourism also has an influence on Regional Original Revenue (PAD) for Local Governments. Kuningan Regency is one of the areas in West Java which has a variety of tourist attractions. One of the leading tourist objects is Panembongan Hill Tour. Panembongan Hill Tourism has potential that needs to be developed. With the existence of competition, the panembongan hill tourism is faced with various opportunities and threats both from outside and from within the country. Based on a survey conducted there was a decrease in the number of visitors during the opening of new tourist attractions, therefore this study was conducted to determine the effect of Information Technology and Innovation on Competitive Advantage to Improve Organizational Performance in Panembongan tourist attractions. The population in this study visitors come to tourist attractions in Panembongan which are domestic tourism and foreign tourists. The number of samples used was 150 respondents. The data collection method is done through a questionnaire method. This study uses structural equation medeling (SEM) analysis techniques using the AMOS 2.1 analysis tool. Keywords: Information Technology, Innovation, Competitive Advantage, Organizational Performance